Orthodontic treatment with the meaw technique following high condylectomy for the treatment of condylar hyperplasia: case series - Diego Fernando López-Buitrago; Santiago Herrera-Guardiola (Universidad de Antioquia, 2018)
Unilateral condylar hyperplasia (UCH) is a pathological condition affecting not only facial appearance and occlusal relationships, but also mandibular joints health. The accurate and timely diagnosis, along with a therapeutic work and a multidisciplinary approach, help reduce the morphological alterations caused by this pathology. Orthodontics plays an important role in the various treatment modalities because of its role not only in presurgical dentoalveolar decompensation but also in dentoalveolar compensation with vertical management when the asymmetry allows it. The following therapeutic proposal describes the treatment of patients with active UCH subjected to high condylectomy surgery immediately after orthodontic dentoalveolar compensation with Multi-Loop Edgewise Archwire (MEAW) for the vertical handling of occlusal canting and maintenance of the orthopedic position of the mandible. All cases were satisfactorily resolved with the same diagnostic and treatment protocol. The conclusion is that, with adequate diagnosis and orthodontic management following condylectomy, non-severe cases of UCH may be treated.